POLITICS AND GOVERNMENT BUREAUCRACY - Purba, Fitriani (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2023)
Although politics must exist in government bureaucracy, they are two different things. On the other hand, political institutions and bureaucrats do not only dominate government bureaucracy. Max Weber argued that independent political forces form bureaucracy. It sits above or below competing political actors. The bureaucracy is positioned as a neutral force, meaning that the bureaucracy is not more inclined to carry out the policies or orders of the governing power, while other political powers are unwilling. However, the bureaucracy prioritizes the interests of the state and the people as a whole so that whoever the political power that governs the bureaucrats and bureaucracy provides the best service to them.